Paine Memorial: A Visual Essay - Traverso, Antonio; Azua, Enrique (Routledge, 2013)
This visual essay is constructed from still images and fragments of an interview with Sara Ramírez conducted in Paine, Chile, in 2010. The essay’s images and text seek to elicit a reflexive and aesthetic response in the reader, calling their attention to the traumatic experience of the relatives and communities of political detainees who became victims of selective kidnapping, torture, summary execution, and disappearance in 1973. The visual-textual arrangement particularly focuses on the complex tension between no-memory and re-constructed memory in the second and third generations of victims, who have grown up in a disfigured social landscape fatally marked by loss, silence, lack, fear and guilt. Of especial significance for debates regarding “postmemory” is the category “unborn children,” which emerged in the course of the interview, as used by Ramírez to refer to children of executed or missing political detainees who, like herself, were born after their parent’s death or disappearance.